2022
DOI: 10.54393/pjhs.v3i04.102
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of Knowledge Regarding Weaning Practices Among Mothers of Gulab Devi Educational Complex

Abstract: Breastfeeding is the process of feeding human milk to a newborn as well as some other type of formula milk or liquid or nonhuman milk. After 6 months, solid foods are introduced to the baby, known as weaning. Objective: To assess the knowledge of the mothers towards weaning practices of children up to 2 years of age. Methods: A cross-sectional study was carried out at the Gulab Devi educational complex in Lahore. A sample of 100 respondents was taken from February 2022 to March 2022. Research questionnaires we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Gohal et al [18], in Jazan, Saudi Arabia, reported that more than one-half of the participants started with liquid components and later switched to solid foods. Opposite to the study results, Rasheed et al [14] showed that more than one-half introduced solid foods to their babies after six months and first introduced rice and cereals to babies. These results may be a return to the poor practice of the participants toward weaning.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Gohal et al [18], in Jazan, Saudi Arabia, reported that more than one-half of the participants started with liquid components and later switched to solid foods. Opposite to the study results, Rasheed et al [14] showed that more than one-half introduced solid foods to their babies after six months and first introduced rice and cereals to babies. These results may be a return to the poor practice of the participants toward weaning.…”
Section: Discussionmentioning
confidence: 78%
“…In the current study, more than two-thirds of the participants (72%) did not believe feeding water, honey, and semisolid foods before four months enhances health. Parallel to these findings, Rasheed et al [14] found that most mothers think cow milk is not good for infants during their 1st month. However, these findings disagreed with Manisha and Khan's [9] study, which revealed that onefifth of mothers believed that giving water, honey, and solid foods before the age of four months would enhance their health.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Child nutrition standards should be observed when a child begins to be given complimentary foods and since pregnancy. Mothers should monitor the growth during the prenatal and postnatal periods 22 . Scientific works in early childhood nutrition have recognized that during the first 1000 days of life, starting from fetal life and beyond, nutrition has a significant effect on health from childhood to adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Section II asked about clinical symptoms that can help define a child's health [13]. In Section III, six questions were asked about introducing complementary foods, time, and patterns of weaning practices [14]. In the last section, food options were given to ask which foods were presented to infants within the first year of life [15].…”
Section: Methodsmentioning
confidence: 99%